Social Studies Methods Students Engaged in Service-Learning: Reciprocity is the Key - Saundra Wetig (Educational Considerations, 2006)
As a social studies educator, I have found myself at the end of each semester reflecting on my preservice teachers’ practicum experiences.
Keywords: Service Learning; Integration; Academic Learning